Two-Step Electrochemical Pretreatment and Electrodeposition of Silver on Stainless Steel. Issue 7 (25th May 2017) - Datta, Susmit; Das, Mitun; Balla, Vamsi Krishna
Abstract : Orthopedic or dental implant associated infection is one of the major healthcare related complications worldwide. These infections are often linked to the cause of implant failures and death together with the huge economic burden. Therefore, in this article we report development of simple two-step electrochemical pretreatment followed by electrodeposition of silver which can impart anti-infection properties to 316L stainless steel implants. Electrochemical pretreatment was performed in different electrolytes, consisting of current modulation - nucleation pulse and growth pulse to tailor the sub-micron porosity characteristics on the surface. Similar modulation of chronoamperometry was applied to tailor Ag deposition in/on the pores created during pretreatment. The experimental results demonstrated that the submicron pits/pores and Ag particle size and density during electrochemical pretreatment and electrodeposition, respectively, can be tailored by changing the nucleation and growth pulse parameters. Deposition of Ag particles inside/on the pores and removal of passive film decreased their loss from the surface thus demonstrating strong potential in ensuring sufficient and long-lasting supply of anti-microbial ions thereby providing desired on-site therapeutic effect.